Educational services in Portuguese museums: a historical contextualization (Cadernos de Sociomuseologia, 2015)
This article proposes to understand what the space for the education in Portuguese museums over the years. The aim is to understand how the educational basis of ideas was developed in the Portuguese museum spaces and understand whether there is openness and receptivity to new views, moves and understandings, new actions, performances and new proposals that qualify the relationship established between the public, the heritage and the museum. By surveying information on the education activities in the Portuguese museums, the records of creations sectors, the documentation relating to the regulation of the function, among other formal and structural issues for the area, the article searches to understand the historical trajectory of educational services in Portuguese museums. Keywords: Museology and Education; Educational Services; Portuguese museums; Educational Action